Extensional and viscoelastic properties of hydrophobically-modified alkali-soluble associative (HASE) polymer solutions - Tan, Hendra. (2008)
The steady shear, dynamic and extensional properties of four model associative polymer solutions (HASE) were examined in this study. The model HASE systems consist of a co-polymer of methacrylic acid/ethyl acrylate (0.49/0.50 mole ratio) with 0.01 mole fraction of hydrophobes of either a CO, CI2, CI6 and C20 alkyl chains. The hydrophobe is extended from the backbone by a spacer chain of ~ 31 moles of polyethylene- oxide (PEO). At low pH, the polymer exists as insoluble latex particles, which dissolve upon neutralization to pH greater than 7. This gives rise to a large increase in the viscosity, which is attributed to hydrophobic associations and the expansion of the polyelectrolyte backbones.